Pengaruh Periklanan dan Kualitas Makanan terhadap Kepuasan Konsumen Restoran All You Can Eat - Pradipta Mahadika; Zurlina Lubis (STIE-JIC, 2022)
‘All You Can Eat’ are restaurants with a self-service model where customers enjoy a mix of food varieties. This research aimed to determine the effect of advertising and food quality on consumer satisfaction in ‘All You Can Eat’ restaurants. A quantitative analysis was conducted from April to July 2021 at Pochajjang restaurant and Oppa Galbi Restaurant, Jakarta. The purpose of this study was to determine the magnitude of the influence of advertising and food quality on consumer satisfaction at the All You Can Eat restaurant. Furthermore, a sample of 127 respondents was obtained using the Isaac and Michael formula. The primary data obtained was processed using SPSS 26 software. The results showed that advertisement contributes 24.8% towards consumer satisfaction, whereas food quality showed 48.2% contributions towards consumer satisfaction. The results indicated that advertising and food quality positively and significantly affected customer satisfaction by 41.8%. Further research should examine other variables apart from advertising and food quality towards consumer satisfaction latent variable.